Merging Cross-Metathesis and Radical Cyclization: A Straightforward Access to 4-Substituted Benzosultams - Feuillastre, Sophie; Pelotier, Béatrice; Piva, Olivier (Synthesis, 2013)
N-Alkyl-N-allyl-2-bromobenzenesulfonamides were functionalized by selective E-cross-metathesis with various alkenes. Subsequent radical cyclization initiated by 2,2′-azobis(isobutyronitrile) and tris(trimethylsilyl)silane gave the corresponding 4-substituted benzosultams directly in moderate-to-good yields.
Keywords: metathesis; cyclizations; radical reactions; sulfonamides; heterocycles